Breast Care 101: A Teaching Tool to Educate Ob/Gyn Students and Residents in Breast Care. (October 2017) - Miller, Jennifer Griffin; Kinney, Sonja; Hueppchen, Nancy
Abstract : OBJECTIVE: To develop breast educational videos to prepare learners for educational experiences in breast care. METHODS: As part of a prior research study, a needs assessment was completed (presented at APGO/CREOG Meeting 2012) indicating insufficient educational resources in breast care topics for Ob/Gyn residents. For this project, three brief (6–12 minute) videos were developed in the following content areas: breast tools including physical exam, breast cancer risk assessment, and understanding breast imaging results. Resident learners were exposed to these videos in preparation for breast care educational experiences (breast clinic.) After utilizing the videos, learners were assessed on their confidence in evaluating patients with breast complaints. In addition, the videos were presented to medical students prior to their clerkship lecture on Breast Complaints. Videos can be accessed at the present time via You Tube: Evaluation of Breast complaints athttps://youtu.be/ruydjeJumag ; Breast Risk Assessment athttps://youtu.be/VAh71__LhL8 ; and Breast Imaging and Diagnosis athttps://youtu.be/Cmn2KA7Kv-k . EVALUATION: Postintervention surveys were completed by Ob/Gyn residents who had the opportunity to the view the videos regarding satisfaction with format and confidence. Postintervention surveys were completed by M3 students after their breast lecture. DISSEMINATION: Plan to distribute video links directly to fellow Ob/Gyn program directors and via AAMC Med Ed Portal. REFLECTIVE CRITIQUE: The goal of this project is to create resources that can be utilized in different venues to support education in breast care. Access to self-directed learning to prepare for educational experiences supports the learner's confidence, skills, and attitudes toward breast care and enhances their educational experiences. Such resources can also be used by learners at the student and resident level in a flipped classroom approach to prepare the learners for case discussion.